Educação ambiental e educação inclusiva : possíveis conexões - Reis, Anderson de Araujo (2016)
This research aimed to understand to what extent the educational process enables connections between Environmental Education - EE and Inclusive Education – IE from the perspective of teachers and education managers. Thus, we sought to examine possible links between the EE and IE based on the Pedagogical Political Project; Identify how environmental and inclusive issues are embedded in pedagogical practices from the speeches of the education managers and teachers; identify conceptions of Environmental Education and Inclusive Education developed by the school; and verify the effects of continuing education in the educational process. The research had an exploratory character and qualitative approach through case study. As methodological procedure to analyzing the political pedagogical project of the State School Teacher Miriam de Oliveira Santos Melo it was used open questionnaire directed to eleven teachers and managers and focus group with seven professionals who have previously answered to the questionnaires. As a result of the research, it was identified that the PPP contemplate at EE and IE which enables the comprehensive development of students in its different aspects, collectively building a school with inclusive, participatory, autonomous and critical perspective. The conception of the teachers and education managers of the researched field allude to subjective education, which their assumptions and goals are focused on the appreciation of different forms of knowledge, stimulate solidarity, equality and respect for human rights, therefore, acceptance of differences. It is also discussed the need for continuing education in the areas of EE and IE. In this sense, it became clear that the assumptions of the EE in the school where the research took place may assist in the process of inclusion of Persons with Disabilities. However, despite EE and IE be present in the pedagogical processes of the Escola Estadual Professora Miriam de Oliveira Santos Melo, until the moment of the research, the teachers did not relate the two educational areas as fundamental in the process of inclusion of students with disabilities in the school context.